Patterns of Opioid Demand after Operative Treatment of Distal Radius Fractures. Issue 4 (3rd April 2023) - Lee, Nayun; Le, Elliot L.H.; Constantine, Ryan; Iorio, Matthew L.
Abstract : Background: The purpose of this study was to evaluate opioid demand after open reduction and internal fixation of distal radius fractures in patients with and without a diagnosis of cannabis use. Methods: The PearlDiver database was queried for all patients who underwent open reduction and internal fixation of distal radius fractures between 2010 and 2020. Patients were categorized into two groups: (1) those with an active diagnosis of cannabis use (case) and (2) those without (control). The primary outcome measure was morphine milligram equivalents per prescription filled within 30 days after surgery. A logistic regression was used to determine potential risk factors associated with increased opioid filling patterns. Results: The rates of prescription refills before and after surgery were congruent in both the case and control populations and did not show significant differences ( P > 0.05). The average morphine milligram equivalents of patients' first opioid prescription was significantly reduced in the case population compared with the control (352.26 versus 480.61 morphine milligram equivalents/prescription, P = 0.005). A history of chronic opioid use was the strongest predictor of prolonged opioid prescription refills after surgery. Conclusions: This study found a significant reduction in opioid volume in patients with a diagnosis of cannabis use who filled an opioid prescription after open reduction and internal fixation of distal radius fractures. Mental health diagnoses, specifically depression, showed an increased risk of multiple opioid prescription refills in patients without a diagnosis of cannabis use.